1 - Mamadou Dia et Mehdi ben Barka, deux nationalistes africains du temps des indépendances – Etude comparative - Monjib, Maâti (Africa Development, 2021)
Senegalese Mamadou Dia (1910-2009) and Moroccan Mehdi Ben Barka (1918-1965) are two leading figures of anti-colonial fight who marked their era and the African continent through their efforts in favour of independence and for the social and political development of their countries. To this end, they were largely involved in the struggle for power that both countries experienced immediately after claiming independence. This study aims to cross-examine the political biographies of the two nationalist leaders. It seeks to look into their actions and discursive productions from a comparative perspective. Its main objective is to better understand the political stances of these two personalities and the interaction of political elites from both countries with their action as well as their ideological and political choices. The study also delves into the national and regional political background in which both men have evolved during the period spanning from the end of World War II to the mid-sixties.